Ginsentides: Cysteine and Glycine-rich Peptides from the Ginseng Family with Unusual Disulfide Connectivity. Issue 1 (December 2018) - Tam, James P.; Nguyen, Giang; Loo, Shining; Wang, Shujing; Yang, Daiwen; Kam, Antony
Abstract Ginseng, a popular and valuable traditional medicine, has been used for centuries to maintain health and treat disease. Here we report the discovery and characterization of ginsentides, a novel family of cysteine and glycine-rich peptides derived from the three most widely-used ginseng species:Panax ginseng, Panax quinquefolius, andPanax notoginseng . Using proteomic and transcriptomic methods, we identified 14 ginsentides, TP1-TP14 which consist of 31–33 amino acids and whose expression profiles are species- and tissues-dependent. Ginsentides have an eight-cysteine motif typical of the eight-cysteine-hevein-like peptides (8C-HLP) commonly found in medicinal herbs, but lack a chitin-binding domain. Transcriptomic analysis showed that the three-domain biosynthetic precursors of ginsentides differ from known 8C-HLP precursors in architecture and the absence of a C-terminal protein-cargo domain. A database search revealed an additional 50 ginsentide-like precursors from both gymnosperms and angiosperms. Disulfide mapping and structure determination of the ginsentide TP1 revealed a novel disulfide connectivity that differs from the 8C-HLPs. The structure of ginsentide TP1 is highly compact, with the N- and C-termini topologically fixed by disulfide bonds to form a pseudocyclic structure that confers resistance to heat, proteolysis, and acid and serum-mediated degradation. Together, our results expand the chemical space of natural products found in ginseng and highlight the occurrence, distribution, disulfide connectivity, and precursor architectures of cysteine- and glycine-rich ginsentides as a class of novel non-chitin-binding, non-cargo-carrying 8C-HLPs.